Portability | MPTCs, fundeps |
---|---|

Stability | provisional |

Maintainer | Edward Kmett <ekmett@gmail.com> |

Safe Haskell | None |

Monads for free

- class Monad m => MonadFree f m | m -> f where
- wrap :: f (m a) -> m a

- data Free f a
- retract :: Monad f => Free f a -> f a
- liftF :: (Functor f, MonadFree f m) => f a -> m a
- iter :: Functor f => (f a -> a) -> Free f a -> a
- iterM :: (Monad m, Functor f) => (f (m a) -> m a) -> Free f a -> m a
- hoistFree :: Functor g => (forall a. f a -> g a) -> Free f b -> Free g b
- toFreeT :: (Functor f, Monad m) => Free f a -> FreeT f m a
- _Pure :: forall f m a p. (Choice p, Applicative m) => p a (m a) -> p (Free f a) (m (Free f a))
- _Free :: forall f m a p. (Choice p, Applicative m) => p (f (Free f a)) (m (f (Free f a))) -> p (Free f a) (m (Free f a))

# Documentation

class Monad m => MonadFree f m | m -> f whereSource

Monads provide substitution (`fmap`

) and renormalization (`join`

):

m`>>=`

f =`join`

(`fmap`

f m)

A free `Monad`

is one that does no work during the normalization step beyond simply grafting the two monadic values together.

`[]`

is not a free `Monad`

(in this sense) because

smashes the lists flat.
`join`

[[a]]

On the other hand, consider:

data Tree a = Bin (Tree a) (Tree a) | Tip a

instance`Monad`

Tree where`return`

= Tip Tip a`>>=`

f = f a Bin l r`>>=`

f = Bin (l`>>=`

f) (r`>>=`

f)

This `Monad`

is the free `Monad`

of Pair:

data Pair a = Pair a a

And we could make an instance of `MonadFree`

for it directly:

instance`MonadFree`

Pair Tree where`wrap`

(Pair l r) = Bin l r

Or we could choose to program with

instead of `Free`

Pair`Tree`

and thereby avoid having to define our own `Monad`

instance.

Moreover, Control.Monad.Free.Church provides a `MonadFree`

instance that can improve the *asymptotic* complexity of code that
constructs free monads by effectively reassociating the use of
(`>>=`

). You may also want to take a look at the `kan-extensions`

package (http://hackage.haskell.org/package/kan-extensions).

See `Free`

for a more formal definition of the free `Monad`

for a `Functor`

.

(Functor f, MonadFree f m) => MonadFree f (ListT m) | |

(Functor f, MonadFree f m) => MonadFree f (IdentityT m) | |

(Functor f, MonadFree f m) => MonadFree f (MaybeT m) | |

Functor f => MonadFree f (Free f) | |

Functor f => MonadFree f (F f) | |

Monad m => MonadFree Identity (IterT m) | |

(Functor f, MonadFree f m, Error e) => MonadFree f (ErrorT e m) | |

(Functor f, MonadFree f m, Monoid w) => MonadFree f (WriterT w m) | |

(Functor f, MonadFree f m, Monoid w) => MonadFree f (WriterT w m) | |

(Functor f, MonadFree f m) => MonadFree f (ContT r m) | |

(Functor f, MonadFree f m) => MonadFree f (StateT s m) | |

(Functor f, MonadFree f m) => MonadFree f (StateT s m) | |

(Functor f, MonadFree f m) => MonadFree f (ReaderT e m) | |

(Functor f, Monad m) => MonadFree f (FreeT f m) | |

Functor f => MonadFree f (FT f m) | |

(Functor f, MonadFree f m, Monoid w) => MonadFree f (RWST r w s m) | |

(Functor f, MonadFree f m, Monoid w) => MonadFree f (RWST r w s m) |

The `Free`

`Monad`

for a `Functor`

`f`

.

*Formally*

A `Monad`

`n`

is a free `Monad`

for `f`

if every monad homomorphism
from `n`

to another monad `m`

is equivalent to a natural transformation
from `f`

to `m`

.

*Why Free?*

Every "free" functor is left adjoint to some "forgetful" functor.

If we define a forgetful functor `U`

from the category of monads to the category of functors
that just forgets the `Monad`

, leaving only the `Functor`

. i.e.

U (M,`return`

,`join`

) = M

then `Free`

is the left adjoint to `U`

.

Being `Free`

being left adjoint to `U`

means that there is an isomorphism between

in the category of monads and `Free`

f -> m`f -> U m`

in the category of functors.

Morphisms in the category of monads are `Monad`

homomorphisms (natural transformations that respect `return`

and `join`

).

Morphisms in the category of functors are `Functor`

homomorphisms (natural transformations).

Given this isomorphism, every monad homomorphism from

to `Free`

f`m`

is equivalent to a natural transformation from `f`

to `m`

Showing that this isomorphism holds is left as an exercise.

In practice, you can just view a

as many layers of `Free`

f a`f`

wrapped around values of type `a`

, where
`(`

performs substitution and grafts new layers of `>>=`

)`f`

in for each of the free variables.

This can be very useful for modeling domain specific languages, trees, or other constructs.

This instance of `MonadFree`

is fairly naive about the encoding. For more efficient free monad implementation see Control.Monad.Free.Church, in particular note the `improve`

combinator.
You may also want to take a look at the `kan-extensions`

package (http://hackage.haskell.org/package/kan-extensions).

A number of common monads arise as free monads,

MonadTrans Free | This is not a true monad transformer. It is only a monad transformer "up to |

(Functor m, MonadError e m) => MonadError e (Free m) | |

(Functor m, MonadReader e m) => MonadReader e (Free m) | |

(Functor m, MonadState s m) => MonadState s (Free m) | |

(Functor m, MonadWriter e m) => MonadWriter e (Free m) | |

Functor f => MonadFree f (Free f) | |

Functor f => Monad (Free f) | |

Functor f => Functor (Free f) | |

Typeable1 f => Typeable1 (Free f) | |

Functor f => MonadFix (Free f) | |

(Functor v, MonadPlus v) => MonadPlus (Free v) | This violates the MonadPlus laws, handle with care. |

Functor f => Applicative (Free f) | |

Foldable f => Foldable (Free f) | |

Traversable f => Traversable (Free f) | |

Alternative v => Alternative (Free v) | This violates the Alternative laws, handle with care. |

(Functor m, MonadCont m) => MonadCont (Free m) | |

Traversable1 f => Traversable1 (Free f) | |

Foldable1 f => Foldable1 (Free f) | |

Functor f => Apply (Free f) | |

Functor f => Bind (Free f) | |

(Eq (f (Free f a)), Eq a) => Eq (Free f a) | |

(Typeable1 f, Typeable a, Data a, Data (f (Free f a))) => Data (Free f a) | |

(Ord (f (Free f a)), Ord a) => Ord (Free f a) | |

(Read (f (Free f a)), Read a) => Read (Free f a) | |

(Show (f (Free f a)), Show a) => Show (Free f a) |

liftF :: (Functor f, MonadFree f m) => f a -> m aSource

A version of lift that can be used with just a Functor for f.

iterM :: (Monad m, Functor f) => (f (m a) -> m a) -> Free f a -> m aSource

Like iter for monadic values.

hoistFree :: Functor g => (forall a. f a -> g a) -> Free f b -> Free g bSource

Lift a natural transformation from `f`

to `g`

into a natural transformation from

to `FreeT`

f

.
`FreeT`

g

toFreeT :: (Functor f, Monad m) => Free f a -> FreeT f m aSource

Convert a `Free`

monad from Control.Monad.Free to a `FreeT`

monad
from Control.Monad.Trans.Free.

_Pure :: forall f m a p. (Choice p, Applicative m) => p a (m a) -> p (Free f a) (m (Free f a))Source

This is `Prism' (Free f a) a`

in disguise

`>>>`

Just 3`preview _Pure (Pure 3)`

`>>>`

Pure 3`review _Pure 3 :: Free Maybe Int`

_Free :: forall f m a p. (Choice p, Applicative m) => p (f (Free f a)) (m (f (Free f a))) -> p (Free f a) (m (Free f a))Source

This is `Prism' (Free f a) (f (Free f a))`

in disguise

`>>>`

Just (Just (Pure 3))`preview _Free (review _Free (Just (Pure 3)))`

`>>>`

Free (Just (Pure 3))`review _Free (Just (Pure 3))`